Delving Into Existential Fatigue and The Search for Meaning in The Play "kapai-kapai" by Arifin C. Noer - Fiqri Abdul Muqit; Adita Widara Putra (Journal of Humanities Research Sustainability, 2024)
Background. The script of the play "Kapai-Kapai" by Arifin C. Noer has long been the subject of discussion in the Indonesian theater world because of its ability to depict existential fatigue and the search for meaning in human life. Purpose. This study aims to conduct a qualitative analysis of the manuscript in order to better understand the themes raised, the characters depicted, and the writing style used by Arifin C. Noer. Method. Through a qualitative approach, this study uses description and interpretation methods to explore the meanings in the manuscript "Kapai-Kapai." Key themes such as existential fatigue, the search for meaning in life, and social criticism are the focus of the analysis, while the main characters such as Mr. Dullah and Mrs. Dullah are studied in depth to understand their motivations, conflicts, and developments throughout the story. An analysis was also carried out on Arifin C. Noer's writing style, including the use of dialogue, monologues, symbolism, and narrative structure. Results. The results of the study show that the manuscript "Kapai-Kapai" presents a complex and in-depth picture of the human condition trapped in a routine of life without a clear direction. Arifin C. Noer manages to portray the despair and uncertainty in the search for meaning in life, while highlighting the relevant social issues in Indonesian society at the time. This manuscript also shows the author's expertise in using symbolism and writing style that invites deep reflection from readers or viewers. Conclusion. The script of the play "Kapai-Kapai" by Arifin C. Noer deeply explores the theme of existential fatigue and the search for meaning in life through complex characters with reflective dialogues, in-depth monologues, and symbols of life's journey. Reflecting on the socio-cultural context of Indonesia, this manuscript also criticizes the reality of society.